Penggunaan Metode Sosiodrama terhadap Hasil Belajar Tematik Siswa Sekolah Dasar - Endang Sri Maruti; Endah Sari; Savira Elva Riani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: The Use of Sociodrama Methods on Thematic Learning Outcomes of Elementary School Students Penelitian aims to improve social skills by using the sociodrama method in the high class of elementary school students. This research uses a quantitative approach with an experimental method (Quasi Experimental Design). The study population was grade V students of SDN 02 Pangongangan with a total of 47 students. Sampling using random sampling techniques. That is to use VA class students totaling 24 students. Data collection uses pre-test and post-test thematic learning outcomes tests. Data analysis using the Liliefors method. The results of data analysis using the Liliefors method obtained the value of L count on the pre-test = 0.1630 < L table = 0.176 and L count on the post-test = 0.1533 < L table = 0.176 . The results of the homogeneity test analysis using the F test obtained F count = 1.371946 < Ftable = 2.01. In the hypothesis test used with the t-test formula, the results of the t-test analysis are obtained t count = 6.25478 > ttable = 2.074. Since t counts > tthe table then H 0 is rejected and H1 is accepted. This means that the use of the Sociodrama method on the thematic learning outcomes of elementary school students is more effective than conventional learning models. In learning activities, students become concentrated and more active in the entire series of learning activities taking place. When expressing opinions in front of friends, students also become more confident, because students are easier to understand the material. Student thematic learning outcomes also increased, namely 87.57% included in the category of completed learning students.